Karakter Komunikatif Fetishisme Komoditas dalam Sistem Kapitalisme di Sepak Bola Dunia - Fadli Muhammad Athalarik (Bulletin of Community Engagement, 2024)
The football industry in the world today has become a very promising industry. Many parties feel the impact, including players, coaches, staff, owners, supporters, and so on. The presence of commodity fetishism in football is one of the impacts. This fetishism has many positive and negative impacts. The purpose of this study is that researchers want to know the communicative character of commodity fetishism in the capitalist system of world football. This study employs a qualitative research approach with descriptive methods. The data collection technique used secondary data in the form of documentation, such as news from the internet and literature from journals. The results of this study show that the implementation of commodity fetishism can be seen in the gap between competitions, especially level one competitions, and those below. In addition, there is a worship of certain players who are actually considered commodities, thus causing fanaticism for most parties, especially fans.  Keywords:  Commodities, Fetishism, The Football Industry